Visualization of the Evolution of Green Marketing Literature: A Bibliometric Review (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The integration of green marketing into corporate strategies represents a paradigmatic shift in responding to global sustainability issues while enhancing competitiveness and socio-ecological commitment. With the rapid growth of literature in this field, a systematic analysis is required to map its conceptual evolution and strategic directions. This study presents a bibliometric analysis of global research trends in green marketing, aiming to identify the intellectual structure, thematic evolution, and knowledge development over the period 2017–2024. Using the Scopus database and the Biblioshiny and VOSviewer tools, 275 peer-reviewed articles were examined through quantitative bibliometric mapping techniques. The analysis reveals an annual publication growth rate of 15.27%, with dominant themes such as “sustainability,” “green marketing,” and “sustainable development.” Thematic mapping visualizations indicate a shift in research focus from product-related technical issues to strategic, social, and consumer behaviour dimensions. Five major thematic clusters were identified, reflecting interdisciplinary approaches encompassing digital marketing strategies, consumer behaviour, corporate social responsibility, supply chain management, and environmental ethics. These findings underscore the significance of integrating green marketing as a sustainable business strategy, not only to enhance corporate image but also to foster more environmentally responsible consumer behaviour. The study provides a conceptual foundation for future inquiries and strategic implications for business practices, affirming the role of green marketing as a catalyst for organizational transformation toward environmental and social sustainability.